Review of "The Pink Tide: Media Access and Political Power in Latin America" edited by Lee Artz (Rowman & Littlefield) - Paula Santa Rosa (Lateral, 2018)
The "Pink Tide" refers to the unprecedented succession of electoral victories of socialist-leaning populist presidents in the region, starting with Chavéz’s victory in 1998. This anthology explores media reforms in countries that most consistently reelected progressive candidates, specifically Venezuela, Bolivia, Ecuador, Uruguay, and Brazil. Through these case studies, Artz seeks to show that the primary indicator of democracy and social justice is the extent to which governments give the population direct access and control of the means of communication. Despite the complexities of the different cases, Artz presses that public participatory media, by promoting and prefiguring a socialist society, is an integral part of the democratic struggle that must be actively and continuously pursued by social movements.